1833. Measuring Influenza HA Stem-Specific ADCC in Human Sera Using Novel Stabilized Stem Nanoparticle Probes - Smatti, Maria K (Open Forum Infect Dis, 2019)
BACKGROUND: Generating a vaccine that confers complete protection and overcomes the high variability among influenza viruses is the major goal in designing a universal influenza vaccine. Currently, there is considerable interest in the broadly neutralizing antibodies (bNAb) targeting the conserved HA stem region. These antibodies have been shown to activate cellular immune responses, such as antibody-dependent cellular cytotoxisity (ADCC), in addition to their neutralization activity. We had previously demonstrated that immunization with H1-based stabilized stem (SS) nanoparticles (np) protects against heterosubtypic lethal challenge with H5N1 influenza virus, despite the absence of detectable H5N1 neutralizing activity. Here, we utilized these novel SS np probes to develop a new protocol to assess the ADCC activity mediated by stem-directed antibodies in human sera. METHODS: Human sera samples were initially screened for binding reactivity to H1 SS trimer using ELISA procedure. Of these, selected samples representing high, moderate, and low binders were further characterized for binding to H1 and H5 SS their corresponding Δstem (Ile45Arg/Thr49Arg) probes, and were analyzed for ADCC activity using a reporter bioassay. RESULTS: The initial screening revealed 82% (73/90) seroprevalence of anti-HA (H1) stem epitope antibodies, as determined by the differential binding to HA SS and it corresponding epitope-mutant probe. Using equimolar amounts, the multivalent presentation of HA SS on np probes induced significantly higher ADCC activity compared with the monovalent SS probes (2- to 6-fold increase). Further, ADCC activity was similarly reported against different influenza group 1 subtypes: H1, H2, and H5. Importantly, ADCC was mediated mainly by antibodies targeting the bNAb-epitope on the HA stem. In conclusion, we developed an assay to measure stem-specific ADCC activity using SS np probes. CONCLUSION: Our results indicate a high prevalence of HA-stem antibodies with cross-reactive ADCC activity. Such assay could be utilized in the assessment of next-generation influenza vaccines. [Image: see text] [Image: see text] [Image: see text] DISCLOSURES: All Authors: No reported Disclosures.